Geomorphological study of Samaria gorge (Crete) using Remote Sensing techniques and GIS. - Vaiopoulos, D.; Vassilopoulos, A.; Evelpidou, N.; Skianis, G. (Congress of Remote Sensing for Environmental Monitoring, GIS Applications, and Geology II, 2002)
In this paper we study Samaria gorge through recognition, recording and visualization of geomorphological characteristics. Geomorphological characteristics collected through Remote Sensing techniques, are compared with those collected through stereoscopic observation of aerial photos and fieldwork. At the first phase, the aerial photos of the studied area were scanned and through selected digital image processing algorithms, the geomorphological characteristics were stressed and recorded. At the second phase a geomorphological map was created based on data derived from stereoscopic observation of the area aerial photos and fieldwork. During fieldwork a GPS was used, which was connected with the GIS in order to immediately record and test the measured characteristic position. Finally the combination of two methods took place in order to develop a geomorphological map.